A STUDY OF THE EFFECTS OF BLASTING VIBRATIONS ON THE NEARBY STRUCTURES - Kumar, Anand (IIT(BHU), 2021)
Abstract is available in the attachment
This Thesis Submitted by Phd Scholar IIT(BHU), Varanasi & Supervised by Prof. Sanjay Kumar Sharma And Dr. Nawal Kishore.
Keywords: BLASTING VIBRATIONS; NEARBY STRUCTURES